Microbial and Molecular Screening of Swimmers Associated with Conjunctivitis from Public Swimming Pools in Erbil Province - Sazan Q. Maulud; Lawin A. Omar; Ahmed Nawzad Hassan; Rastee H. Saeed (Al-Mustansiriyah Journal of Science)
Public swimming pools, if not treated well could work as a reservoir of many microorganisms that cause infections among swimmers. Conjunctivitis is one of those common infections that resulted from microbial and non-microbial agents, microbial conjunctivitis caused by viral (mainly Human adenovirus HAdVs) and bacterial infections. This study aims to investigate the prevalence of microbial causative agents of swimming pool conjunctivitis and evaluating the swimming pools in terms of health and the extent of contamination in Erbil province. Eighty-eight specimens were isolated and identified from the swimmers showing signs and symptoms of swimming pool conjunctivitis from different public swimming pools in Erbil city from January to the end of February 2020. Sample identified using bacteriological methods, serology test, and nested PCR for detection of HAdVs. The swimmers samples consisted of 60 males and 28 females, and they were aged between 16-56 years. The obtained results showed that, out of 88 samples, 36 (40.91%) detected as a viral infection and 29 (32.95%) as bacterial infection, while, 23 (26.13%) showed no growth (non-microbial infection). Frequency of swimming pool conjunctivitis among male and female was 60 (68.2%) and 28 (31.8%) respectively. Depending on the obtained results, it can be concluded that conjunctivitis could result from viral, bacterial, and non-microbial agents, a viral infection is the main cause followed by a bacterial infection, also public swimming pools are not a safe place and swimmers are subjected to infection by different pathogens.